محور التلقي في الأدب التفاعلي (رواية ظلال العاشق لمحمّد سناجلة أنموذجا) (مجلة إحالات, 2025)
تتنزّل أهميّة هذه المداخلة في كونها تحاول رصد بعض الإشكاليات التي تطرحها عمليّة تلقي النص الرقمي في مثل هذا النموذج من الأدب، خاصة إذا أخذنا بعين الاعتبار طبيعة المجتمع العربي الذي تعتبر فيه ظاهرة الرقمنة تجربة جديدة وفتيّة، أضف إلى ذلك أنّه (الأدب الرقمي) يشكّل تجلي أدبي غير مألوف للمتلقي، لذا يمثّل التعامل معه في ظلّ غياب شروط معرفيّة ونقديّة واعية إخلالا بمنطق تلقيه، وذلك بحكم أنّ الأدب الرقمي لا يغادر الحاسوب إنتاجا وقراءة ونشرا، والحاسوب ليس مجرّد وسيط للنّشر في هذه الحالة إنّه يتجاوز ذلك إلى إلحاق تعديلات جوهريّة على النصّ.The importance of this intervention is revealed in that it tries to monitor some of the problems posed by the process of receiving the digital text in such a form of literature, especially if we take into account the nature of Arab society in which the phenomenon of digitization is a new and young experience, in addition to that (digital literature) is a manifestation Literary is unfamiliar to the recipient, so dealing with it in the absence of cognitive and critical conditions constitutes a violation of the logic of its reception, and that is because digital literature does not leave the computer in production, reading and publishing, and the computer is not just a medium for publishing in this case it goes beyond that to substantial changes to the text.